Praktik Pemberian Makan Prelakteal di Daerah Urban dan Rural Indonesia: studi data Survei Dasar Kesehatan Indonesia 2017 - Purwanti, Rachma; Rahadiyanti, Ayu; Kurniawati, Dewi Marfu'ah; Irawan, Galuh Chandra (Poltekkes Kemenkes Kendari, 2022)
Based on WHO data, globally, the achievement of exclusive breastfeeding is still relatively low (<50%). Pre-lacteal feeding is a challenge for the success of exclusive breastfeeding. This study aims to analyze the relationship between residence in rural and urban areas with the practice of pre-lacteal feeding and the type of pre-lacteal food given. The study use secondary data from Indonesian Demographic and Health Survey (IDHS)-2017 with a cencus block sample frame from the results of the 2010 population cencus. The variables studied were the subject's residence (rural-urban), pre-lacteal feeding, and the type of pre-lacteal food given. The subjects of this study were 8841 subjects. Data analysis carried out included univariate and bivariate analysis. There was no relationship between residence in rural/urban areas and the practice of pre-lacteal feeding (p>0.05). There was a relationship between residency in rural/urban areas and the type of pre-lacteal food given, namely milk other than breast milk, plain water, sugar water, formula milk, honey, coffee, and other fluids (p<0.001; p=0.003; p<0.001 ; p<0.001; p<0.001; p=0.011; p<0.001). Water, sugar water, honey, and coffee are pre-lacteal foods frequently given in rural areas. Milk other than breast milk and formula milk is pre-lacteal food frequently given in urban areas. Residency in rural/urban areas is not related to pre-lacteal feeding practices but is related to the type of pre-lacteal food given. Suggestion: it is necessary to conduct a national study to analyze the factors related to the types of pre-lacteal food given in rural and urban areas.